2021
DOI: 10.1016/j.gie.2021.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Pyloric dilation with the esophageal functional lumen imaging probe in gastroparesis improves gastric emptying, pyloric distensibility, and symptoms

Abstract: Background and Aims: The role of decreased pyloric distensibility in gastroparesis as measured by the endolumenal functional luminal imaging probe (EndoFLIP) has been receiving increasing attention. In this study, we present clinical outcomes to pyloric dilation with the esophageal FLIP (EsoFLIP) in regard to gastric emptying, symptom evolution, and FLIP metrics.Methods: Patients evaluated for gastroparesis (gastric emptying studies of t 1/2 !180 minutes during 13 C-octanoic acid breath test and/or gastric rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
(50 reference statements)
1
8
0
1
Order By: Relevance
“…Pyloric botulinum toxin (Botox) injection and pneumatic dilation are thought to work by a similar mechanism [12][13][14]. The efficacy of dilation and Botox as stand-alone treatments is controversial [3,15,16]. In fact, their use is not recommended in the most recent guidelines by the American College of Gastroentology [3].…”
mentioning
confidence: 99%
“…Pyloric botulinum toxin (Botox) injection and pneumatic dilation are thought to work by a similar mechanism [12][13][14]. The efficacy of dilation and Botox as stand-alone treatments is controversial [3,15,16]. In fact, their use is not recommended in the most recent guidelines by the American College of Gastroentology [3].…”
mentioning
confidence: 99%
“… 111 Subsequent studies on impedance planimetry measurements reaffirmed similar correlation between an increased pyloric distensibility and improved gastroparesis symptoms, whether the pyloromyotomy was performed by G-POEM or by an EsoFLIP-controlled pyloric dilation. 127 - 129 Gastric emptying was also found to be decreased after G-POEM when improved pyloric indices and symptoms were observed. 129 , 130 Although there is prognostic benefit of intra-procedural pyloric evaluation using EndoFLIP Ⓡ , the cost-effectiveness of its routine use remains to be further verified.…”
Section: Treatmentmentioning
confidence: 88%
“…No complications were shown with the hydraulic balloon dilation, used up to 20 mm. Recently, the EsoFLIP, combining EndoFlip measurement, and hydraulic dilation at a diameter up to 30 mm have been assessed and led to a symptomatic improvement in 57% of patients at 4 months 65 . The study by Jehangir et al reported symptomatic improvement with pyloric dilation after a previous pylorotomy in 5 patients out of 13 63 .…”
Section: Endoscopic Therapies Targeting the Pylorusmentioning
confidence: 99%